The relationship between tax structures and income inequality - Carlândia Fernandes; Marcos Roberto Vasconcelos; Marina Silva da Cunha; Thomas Obst (Desarrollo y Sociedad, 2025)
The global rise in income inequality has heightened interest in how fiscal policy—particularly the composition of tax revenues—affects income distribution. This study examines the relationship between government revenues from direct and indirect taxes and income inequality, contributing to the tax incidence literature through three key innovations: it focuses on a recent period (2000–2012), compares countries with different income levels and tax structures, and addresses endogeneity using the System Generalized Method of Moments (System GMM) estimator. The empirical analysis reveals that a greater reliance on indirect taxation is associated with higher income inequality, while a larger share of direct taxes correlates with reduced inequality. These patterns hold across both OECD and non-OECD countries. Given the higher Gini coefficients observed in non-OECD economies, the findings highlight the importance of enhancing tax progressivity as a policy strategy to reduce income disparities and promote more equitable economic development.